Catalytic Reductive Amination of Aldehydes and Ketones With Nitro Compounds: New Light on an Old Reaction - Sukhorukov, Alexey Yu. (Frontiers in Chemistry, 2020)
Reductive amination of carbonyl compounds with primary amines is a well-established synthetic methodology for selective production of unsymmetrically substituted secondary and tertiary amines. From the industrial and green chemistry perspective, it is attractive to combine reductive amination with the synthesis of primary amines in a single one-pot catalytic process. In this regard, nitro compounds, which are readily available and inexpensive feedstocks, received much attention as convenient precursors of primary amines in such processes. Although direct reductive coupling of nitro compounds with aldehydes/ketones to give secondary and tertiary amines is known since 1940’s, breakthrough in this area was made in the last decade owing to the development of highly efficient and selective non-noble metal-based catalysts. In this short overview, recent progress in the methodology of the reductive amination with nitro compounds is summarized together with applications to the synthesis of bioactive amines and heterocycles. Also remaining challenges in this field are analyzed.